Relationship between Earnings Response Coefficient of insurance firms and exgrowth opportunities, earned premium incomes and commissions in Malaysia - Cheng, Fan Fah; Lee, Hui Sin (Canadian Center of Science and Education, 2014)
The insurance industry plays the roles of intermediary, provider of financial services and risk transferor. These important roles have created strong demand for insurance products. Strong financial fundamentals combined with industry strength are vital for insurance-based companies to continuously do well in their business. This paper analyses the Earnings Response Coefficients (ERCs) and the financial performance of insurance-based companies in Malaysia. This analysis covers a period of 5 years from the year 2007 to the year 2011.This study also investigates the relationship between growth opportunity for the insurance industry in Malaysia and earned premium income, net investment income, net claims incurred, commissions paid, total assets and total liabilities as the specific factors of an insurance firm. As discovered in other studies, ERCs are found to be significant. In addition, among the six variables, only commission paid shows a significant result in affecting growth opportunities. A significant negative relationship is found between commissions paid and growth opportunities for the insurance industry in Malaysia. The significant relationship suggests that insurance companies should adequately implement or administer arrangements in their commissions paid policy.